Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1037/0893-164x.21.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of change in adolescent substance use and symptomatology: Impact of paternal and maternal substance use disorders.

Abstract: The effects of paternal and maternal substance use disorders (SUDs) on trajectories of change in adolescent offspring nicotine, alcohol, and drug use and symptomatology were investigated in a population-based sample of adolescent twins (N = 1,514). Adolescent and parental substance phenotypes were assessed when most adolescents were 11 years old, with 2 assessments of adolescents approximately every 3 years thereafter. Growth curves were fit using hierarchical linear modeling. Results indicated acceleration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 49 publications
3
34
0
4
Order By: Relevance
“…This explanation is in line with a review study showing that risk factors for harmful alcohol use vary across different age groups [18]. Moreover as seen in other studies [13,15,33,35], our results showed that males were at higher risk for problem drinking than females.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This explanation is in line with a review study showing that risk factors for harmful alcohol use vary across different age groups [18]. Moreover as seen in other studies [13,15,33,35], our results showed that males were at higher risk for problem drinking than females.…”
Section: Discussionsupporting
confidence: 81%
“…Those few studies that studied these differential influences again reported mixed findings. Walden et al [35] reported that both fathers' and mothers' drinking was related to adolescent heavy drinking, as did McGue et al [20] who further showed this result to be stronger for biological than adoptive parents. In contrast, Reifman et al [27] reported that only mother's drinking was related to heavy drinking among adolescents, while another study suggested that neither paternal nor maternal alcohol use was related to adolescent problem drinking [37].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…A transmissão transgeracional dessa síndrome é um tema de estudo frequente na literatura nacional e internacional. Pais que fazem uso de alguma droga servem de modelo tanto para meninos quanto para meninas na experimentação e no início do contato com álcool e outras drogas [15][16][17][18][19] .…”
Section: Transmissão Transgeracional Do Uso De áLcool E Drogasunclassified
“…Segundo Walden et al 18 , adolescentes com pais usuários de drogas apresentam um índice muito maior de uso de nicotina nessa fase. Pélissolo et al 20 relatam que o uso de ansiolíticos e hipnóticos entre as adolescentes está extremamente vinculado ao uso desses medicamentos pelos pais, principalmente pelas mães, no caso das meninas.…”
Section: Transmissão Transgeracional Do Uso De áLcool E Drogasunclassified